Estratégia ativa no mercado acionário brasileiro: otimização ou aposta nas winners ? - Reis, Cauê Márcio dos (2011)
This paper analyzes the risk-return performance, graphically and quantitatively - measured under various metrics, of active strategies available for a Brazilian investor who chooses to compose dynamic portfolios with stocks traded in BOVEPSA, Bolsa de Valores de São Paulo. The strategies used here are based on: (i) "betting" in Sharpe and Treynor winners securities the previous year, composing an equalweighted portfolio or (ii) optimizing these two widely used performance metrics, and the defining the weights. To summarize, in periods of economic boom - until 2007 and during 2009 - when dealing with the trade-off between using more sophisticated portfolio composition techniques, the Brazilian investor would have gotten a much higher accumulated nominal return when using the Sharpe index optimization – over 4000% between July 1995 and December 2007, for example – vis-à-vis other strategies and even when compared to larger stock mutual funds or to the market and industry benchmarks, which does not exceed 2500%. In terms of risk-return performance, the betting strategies based on Sharpe and Treynor winners are the most appropriate. In periods of financial crisis, observing any performance measure, an investor should have chosen for a passive strategy.